2001
DOI: 10.1038/sj.bmt.1703290
|View full text |Cite
|
Sign up to set email alerts
|

Secondary thyroid carcinoma after allogeneic bone marrow transplantation during childhood

Abstract: Summary:The aim of this study was to evaluate the incidence and risk factors related to secondary thyroid carcinoma (STC) in patients who have undergone allogeneic BMT during childhood. Data related to the primary hematological disorder and BMT procedure were obtained from the records of 113 patients (42 F; 71 M) who underwent BMT before the age of 18 (median 10.0 years; range 1.7-18.0) and survived more than 3 years after transplant with a median follow-up of 10.1 years (range 3.0-19.0). Sixteen received cran… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

4
17
0

Year Published

2005
2005
2019
2019

Publication Types

Select...
3
3
2

Relationship

0
8

Authors

Journals

citations
Cited by 44 publications
(21 citation statements)
references
References 20 publications
4
17
0
Order By: Relevance
“…treated with 1200 cGy. The other study focused on patients with thyroid carcinoma only, which was found in eight (7%) of the 113 patients investigated with a median of 8.5 years (range: 3.1-15.7) after TBI (24). This frequency was similar to the 8% reported here for thyroid carcinoma, with a similar follow-up period.…”
Section: Discussionsupporting
confidence: 61%
See 2 more Smart Citations
“…treated with 1200 cGy. The other study focused on patients with thyroid carcinoma only, which was found in eight (7%) of the 113 patients investigated with a median of 8.5 years (range: 3.1-15.7) after TBI (24). This frequency was similar to the 8% reported here for thyroid carcinoma, with a similar follow-up period.…”
Section: Discussionsupporting
confidence: 61%
“…With the increasing use of ultrasound scans and FNAB, thyroid carcinoma tends to be diagnosed very accurately at early stages (51). Only two other retrospective studies reported the results of ultrasound examinations for the detection of thyroid nodules and/or carcinoma during the follow-up of patients receiving TBI as part of conditioning regimens for HSCT during childhood (22,24). One of these studies on 42 patients surviving for at least 10 years after TBI, in which earlier effects were not investigated, showed that nodules were present in 60% of the patients and that thyroid carcinoma occurred in six (25%) of the 24 patients with nodules after a median of 12 years of follow-up (22), consistent with the diagnosis of thyroid carcinoma for 29% of the nodules in our study.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…The cause of death was not specified. Cohen et al 12 reported that eight out of 113 patients developed thyroid cancer at a median of 10 years after BMT. Only one patient had a palpable nodule, but ultrasonography was performed annually.…”
Section: Discussionmentioning
confidence: 99%
“…The intensive conditioning regimens required in most cases often result in impaired growth and reduced final height, especially if unfractionated TBI is part of the conditioning regimen (1). TBI can impair growth both directly, by damaging the epiphyseal growth plates, and indirectly, by decreasing GH secretion, or by causing hypogonadism or hypothyroidism (2).…”
mentioning
confidence: 99%